2002
DOI: 10.1124/jpet.300.1.227
|View full text |Cite
|
Sign up to set email alerts
|

Histamine Regulation of Interleukin-18-Initiating Cytokine Cascade Is Associated with Down-Regulation of Intercellular Adhesion Molecule-1 Expression in Human Peripheral Blood Mononuclear Cells

Abstract: In the previous study, we demonstrated that interleukin (IL)-18 up-regulated intercellular adhesion molecule-1 (ICAM-1) expression on monocytes in human peripheral blood mononuclear cells (PBMC) and that heterotypic interaction between monocytes/T or NK cells through ICAM-1/LFA-1 intensified the production of IL-12, interferon-␥ (IFN-␥), and tumor necrosis factor-␣ (TNF-␣) in PBMC. In the present study, we demonstrate that histamine inhibited the ICAM-1 expression in monocytes induced by IL-18 using flow cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
20
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 37 publications
1
20
0
1
Order By: Relevance
“…In the present study, we found that IL-18, a proinflammatory cytokine associated with various pathologic conditions including RA, dose-dependently enhanced the ability of RA synovial T cells or PHA-prestimulated T lymphocytes to induce production of TNF␣ and IL-1␤, but not IL-10, from resting monocytes upon direct cell-cell contact. Recently, Takahashi et al (25) reported that IL-18 inhibited IL-10 production in cultured PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we found that IL-18, a proinflammatory cytokine associated with various pathologic conditions including RA, dose-dependently enhanced the ability of RA synovial T cells or PHA-prestimulated T lymphocytes to induce production of TNF␣ and IL-1␤, but not IL-10, from resting monocytes upon direct cell-cell contact. Recently, Takahashi et al (25) reported that IL-18 inhibited IL-10 production in cultured PBMCs.…”
Section: Discussionmentioning
confidence: 99%
“…B7.1 and B7.2 have different affinities for their binding partners on T cells, CD28 and CTLA-4, and the differential roles of B7.1 and B7.2 have been suggested for the initial, sustained T cell activation or termination of T cell activation (20,21). Previously, we demonstrated that histamine regulated the IL-18-initiating cytokine cascade through down-regulation of ICAM-1 expression on monocytes (23). The changes may result in a shift of Th1/Th2 balance toward Th2 dominance (23,24).…”
mentioning
confidence: 99%
“…Previously, we demonstrated that histamine regulated the IL-18-initiating cytokine cascade through down-regulation of ICAM-1 expression on monocytes (23). The changes may result in a shift of Th1/Th2 balance toward Th2 dominance (23,24). Thus, many kinds of chemical mediators in inflammation may modulate immune responses by regulation of the expression of adhesion molecules.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the action of histamine on NK cell function has recently gained attention, providing a potential link between a key factor in allergic asthma and NK cells. Histamine interferes with ICAM-1/LFA-1-dependent cytokine production in monocyte/NK-cell and T-cell cocultures (20) and protects NK cells against apoptosis induced by oxygen radicals (21).…”
mentioning
confidence: 99%